CAMPUR KODE DALAM NOVEL ALSTER LAKE KARYA AURYN VIENTANIA - Della Kurnia Putri Anthoni; Charlina; Oki Rasdana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Code-mixing is a linguistic phenomenon that emerges in bilingual or multilingual communities, and is often found in written literary works such as novels. This study aims to identify the types, forms, and functions of code-mixing present in the novel Alster Lake by Auryn Vientania. The research uses a descriptive qualitative method with the novel Alster Lake as the main data source. The research data consists of dialogues between characters and story narrations containing code-mixing. The results identified three forms of code-mixing (word, phrase, and clause), three types of code-mixing (inner, outer, and hybrid/mixed), and four functions of code-mixing (showing respect, emphasizing a specific intention, indicating self-identity, and the influence of the conversation material). The most dominant form of code-mixing is the word level (89 data). The most dominant type of code-mixing is outer code-mixing (122 data), involving English and German. Meanwhile, the most dominant function of code-mixing is the influence of the conversation material (76 data). The use of this code-mixing serves to build character depth, create atmosphere, and reflect the social reality of contemporary multilingual communities.